2003
DOI: 10.1046/j.1471-4159.2003.01683.x
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal roles of α‐melanocyte‐stimulating hormone and the melanocortin 4 receptor in leptin stimulation of prolactin secretion in rats

Abstract: Leptin, the obese gene product, was reported to stimulate prolactin (PRL) secretion, but the neuroendocrine mechanism underlying this hormonal response is largely unknown. Thus, in this study we examined the involvement of several important PRL regulators in the leptin-induced PRL secretion in male rats. Compared with the values in normally fed rats, food deprivation for 3 days significantly decreased both PRL and leptin levels in the plasma. These changes were reverted to normal by a 3-day constant infusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 66 publications
(85 reference statements)
1
7
0
Order By: Relevance
“…It is possible that α-MSH acting at the pituitary level prevented the fall in pituitary prolactin content in the Tg-MSH mice. This would be consistent with the stimulatory effect of α-MSH on prolactin release reported in vitro in cultured lactotrophs[45]. However, given that basal and stress-induced prolactin release is suppressed in Tg-MSH mice, the effects of α-MSH on the dopaminergic regulation of prolactin appears to predominate.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It is possible that α-MSH acting at the pituitary level prevented the fall in pituitary prolactin content in the Tg-MSH mice. This would be consistent with the stimulatory effect of α-MSH on prolactin release reported in vitro in cultured lactotrophs[45]. However, given that basal and stress-induced prolactin release is suppressed in Tg-MSH mice, the effects of α-MSH on the dopaminergic regulation of prolactin appears to predominate.…”
Section: Discussionsupporting
confidence: 87%
“…This appears to be via stimulation of the MC3-R that is expressed by lactotrophs [25]. There is also a report that an α-MSH antiserum attenuates stimulation of prolactin by leptin [45]. Thus α-MSH may modulate prolactin release at both the pituitary and hypothalamic level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports indicated that HS024 diminishes proestrous and leptin-induced surges of LH and PRL [46, 47, 48, 49]. The mechanisms involved in the control of these surges are different from those involved in maintaining basal levels of PRL and LH.…”
Section: Discussionmentioning
confidence: 95%
“…Serotonergic raphe neurons have been shown to lack the long isoform of leptin receptors (Ob-Rb) [7] and serotonin turnover was unaffected in several brain areas of normal rats after 3 days of intraperitoneal leptin infusion [8]. Basal and potassium-stimulated serotonin overflow were unaltered by the addition of leptin to synaptosomes or superfusion preparations of rat hypothalami [9,10].…”
Section: Introductionmentioning
confidence: 99%